Neuroprotective Effects of Serpina3k in Traumatic Brain Injury - Jing, Yao; Yang, Dianxu; Fu, Yimu; Wang, Wei; Yang, Guoyuan; Yuan, Fang; Chen, Hao; Ding, Jun; Chen, Shiwen; Tian, Hengli (Frontiers in Neurology, 2019)
Traumatic brain injury (TBI) is a major cause of disability and mortality worldwide, in part resulting from secondary apoptosis of neurons in peri-contusion areas. Serpina3k, a serine protease inhibitor, has been shown to inhibit apoptosis in injury models. In this study, we investigated the anti-apoptotic function of serpina3k in vivo using a mouse model of TBI, as well as the underlying neuroprotective mechanism in vitro using the SH-SY5Y human neuroblastoma cell line. TBI was induced in adult male C57BL/6 mice using controlled cortical impact. Serpina3k protein was intravenously administered at a concentration of 0.5 mg/kg twice daily for up to 14 days. SH-SY5Y cells were subjected to biaxial stretch injury and then treated with different concentrations of serpina3k. We found that endogenous serpina3k protein levels were elevated in peri-contusion areas of the mouse brain following TBI. Serpina3k-treated mice had fewer apoptotic neurons, lower levels of oxidative stress, and showed greater recovery of neurological deficits relative to vehicle-treated mice. Meanwhile, in the SH-SY5Y cell injury model, serpina3k at an optimal concentration (150 nM) inhibited the generation of intracellular reactive oxygen species, abrogated changes of the mitochondrial membrane potential, and reduced the phospho-extracellular regulated protein kinases (p-ERK)/ERK, phospho-P38 (p-P38)/P38, B cell lymphoma (Bcl)-2-associated X protein/Bcl-2, and cleaved caspase-3/caspase-3 ratios, thereby reducing the apoptosis rate. These results demonstrate that serpina3k exerts a neuroprotective function following TBI and thus has therapeutic potential.